New Taxa and Taxonomic Revisions to the Poraniidae (Valvatacea; Asteroidea) with Comments on Feeding Biology - Mah, C. L.; Foltz, D. W. (Zootaxa, 2014)
New molecular phylogenetic data and new specimens provide the basis for a revision of the family Poraniidae. We present molecular phylogenetic data for five out of 11 genera in the Poraniidae including a newly discovered taxon from the North Pacific. Bathyporania ascendens nov. gen., nov. sp., is described from Davidson Seamount (35º43’N, 122º43’W). Another newly discovered poraniid taxon, Clavaporania fitchorum nov. gen, nov. sp. is described from south of Macquarie Island (56º21’S, 158º 28’E) but was not included in the analysis. Revision of the Poraniidae has been undertaken. We present two new genera and reinstate the previously synonymized genus Glabraster and return Culcitopsis to genus level. The genus Porania sensu Clark (1993) and Clark and Downey (1992) is not monophyletic. Porania,Poraniomorpha and Poraniopsis are revised. In situ feeding observations of Bathyporania are described and compared with other poraniid feeding accounts.